University management: contributions for nurses who are faculty members and managers - Kamylla Santos da Cunha; Carolina Kahl; Cintia Koerich; José Luís Guedes dos Santos; Gabriela Marcellino de Melo Lanzoni; Alacoque Lorenzini Erdmann
ABSTRACT Objective: To comprehend how university management contributes on the performance of nurses who are professors and managers in a public university. Method: Qualitative research anchored on the Grounded Theory. The setting to collect the data was a public university in south Brazil and it happened between May and September of 2016. A total of 19 nurses took part in the study, all of them also faculty members and managers that were divided in two sample groups. Results: Two subcategories were created: the comprehension that university management improves the faculty performance; obtaining a wider view of the university. Final considerations: The contributions of university management for faculty nurses who are managers are mainly on the personal and professional satisfaction through the production and dissemination of knowledge, reflecting positively on the refinement of the teaching competences to train Nurses with knowledge, technical skills and cognitive abilities to answer society's needs.